The role of oxidative stress in the pathogenesis of infections with coronaviruses - Gain, Chandrima; Song, Sihyeong; Angtuaco, Tyler; Satta, Sandro; Kelesidis, Theodoros (Frontiers in Microbiology, 2023)
Coronaviruses can cause serious respiratory tract infections and may also impact other end organs such as the central nervous system, the lung and the heart. The coronavirus disease 2019 (COVID-19) has had a devastating impact on humanity. Understanding the mechanisms that contribute to the pathogenesis of coronavirus infections, will set the foundation for development of new treatments to attenuate the impact of infections with coronaviruses on host cells and tissues. During infection of host cells, coronaviruses trigger an imbalance between increased production of reactive oxygen species (ROS) and reduced antioxidant host responses that leads to increased redox stress. Subsequently, increased redox stress contributes to reduced antiviral host responses and increased virus-induced inflammation and apoptosis that ultimately drive cell and tissue damage and end organ disease. However, there is limited understanding how different coronaviruses including SARS-CoV-2, manipulate cellular machinery that drives redox responses. This review aims to elucidate the redox mechanisms involved in the replication of coronaviruses and associated inflammation, apoptotic pathways, autoimmunity, vascular dysfunction and tissue damage that collectively contribute to multiorgan damage.